(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Epilepsy is one of the most common neurological disorders, affecting approximately 65 million people of all age groups worldwide. Brivaracetam is a classic antiepileptic drug, which exhibits potent therapeutic efficacy in controlling seizures. Aiming to enhance the nasal administration of drug using the nose-to-brain pathway allows direct targeting into the brain, avoiding the first- pass effect, bypassing the BBB & improve therapeutic efficacy. In this research, the formulation of Brivaracetam-loaded NE was developed using Oleic acid, Tween 80, PEG 400 and water via the Spontaneous emulsification method. A pseudo-ternary phase diagram was constructed to determine the ideal ratio of oil and surfactant/co-surfactant. Characterization studies like SEM analysis, Thermodynamic stability studies, droplet size, PDI, Zeta potential, viscosity and pH, drug content, EE%, and In-vitro drug release. The optimized Brivaracetam-loaded Nano emulsion had a globule size of 161.7 nm, a PDI of 0.253, a zeta potential of -28.9 mV, and EE% of 92.3%, SEM images, drug content of 71.7%. In-vitro drug release studies showed 98% sustained drug release over 8 hours (R2 = 0.993, Higuchi model). The development of BRV-NE may provide a promising approach for the effective delivery of Brivaracetam in the brain, improving the bioavailability of Brivaracetam for the better management of epilepsy.